High-pressure piston type hydrogen compressor cylinder surface PVD coating and preparation process thereof
By employing laser micro-texturing and multi-layer composite PVD coating technology, the problems of coating peeling, hydrogen permeation, and wear in traditional electroplating hard chrome processes under high-pressure hydrogen environments have been solved. This has resulted in a cylinder surface with high adhesion, low friction, excellent corrosion resistance, and high hardness, ensuring the safe and reliable operation of the high-pressure hydrogen compressor.
Patent Information
- Application Number
- CN202511284440.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional electroplating hard chrome is prone to coating peeling, hydrogen permeation, and wear of seals in high-pressure hydrogen environments, leading to safety hazards and limited gloss.
A PVD coating was prepared on the surface of the cylinder of a high-pressure reciprocating hydrogen compressor by using laser microtexturing and plasma activation treatment, combined with multilayer composite structure and rare earth doping technology. The coating includes substrate laser microtexturing, transition layer multi-arc-sputtering alternating deposition, Si/B co-doped CrAlN/CrN superlattice support layer, TiAlSiN-Y2O3 nanocomposite barrier layer and gradient Ti-WC-DLC surface functional layer.
It significantly enhances the adhesion between the coating and the substrate, blocks hydrogen permeation pathways, reduces the coefficient of friction, improves corrosion resistance and hardness, and enhances the reliability and safety of the cylinder block in a high-pressure hydrogen environment.
Smart Images

Figure BDA0005588424540000061 
Figure BDA0005588424540000071 
Figure BDA0005588424540000072
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology for compressor cylinder surfaces, and particularly to a PVD coating on the surface of a high-pressure piston hydrogen compressor cylinder and its preparation process. Background Technology
[0002] High-pressure reciprocating hydrogen compressors are key equipment in the hydrogen energy industry chain. Their core components, such as the compressor cylinder, piston, and cylinder liner, need to operate stably in a high-pressure, high-purity hydrogen environment for a long time. Hydrogen medium has the characteristics of low density, small molecular size, and strong permeability. Moreover, hydrogen under high pressure can easily induce hydrogen embrittlement in materials, which places extremely high demands on the wear resistance, corrosion resistance, and hydrogen permeability resistance of the inner surface of the cylinder.
[0003] Traditional cylinder block surface treatment technology mainly employs electroplating hard chrome. While this process provides a certain level of hardness and wear resistance, it has the following inherent drawbacks: First, the adhesion between the electroplated chrome layer and the substrate is limited, making it prone to peeling under alternating loads; second, the electroplated layer contains microcracks and porosity defects, allowing high-pressure hydrogen to penetrate into the substrate and cause hydrogen embrittlement; finally, the surface finish achieved by traditional electroplating is limited, leading to dry friction with the seals, which accelerates seal wear, ultimately resulting in seal failure and hydrogen leakage, posing serious safety hazards.
[0004] Therefore, it is necessary to solve the above problems by developing a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder and its preparation process. Summary of the Invention
[0005] The purpose of this invention is to provide a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder and its preparation process, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A process for preparing a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder includes the following steps:
[0008] Step 1, Substrate Laser Microtexturing and Plasma Activation: A pulsed fiber laser is used to fabricate a micro-dimple array on the cylinder liner and piston surface. The pulsed laser forms a regular microstructure on the cylinder surface, significantly increasing the coating contact area, providing mechanical interlocking anchor points, and enhancing the physical adhesion between the coating and the substrate; and then, through Ar… + / H2 hybrid plasma etching removes the oxide layer and generates a nanoscale activated surface. High-energy ion bombardment thoroughly removes the oxide layer and generates a nanoscale activated surface, which promotes atomic-level bonding of subsequent coatings and reduces the risk of hydrogen permeation at the interface.
[0009] Step 2, Alternating Multi-Arc Sputtering Deposition of Transition Layer: A Cr layer is deposited alternately by multi-arc ion plating and a WC-La2O3 layer by magnetron sputtering for 3-5 cycles. The Cr layer provides high bonding strength, while the WC layer enhances hardness and thermal stability. The alternating deposition forms a gradient thermal expansion transition, relieving interlayer stress. La2O3 is a rare-earth doped phase. Nanoscale dispersion is achieved through high-energy ball milling of the pre-composite target. High-energy ball milling is used to composite La2O3 / CeO2 nanoparticles with Cr / WC powder. The uniformity deviation of the target composition is ≤1.5 at.%. In the high-energy ball milling method, the ball-to-material ratio is 10:1, the rotation speed is 300 rpm, and the time is 2 hours. Mechanochemical action achieves uniform dispersion of rare-earth nanoparticles in the target, refines grain boundaries, and forms hydrogen traps, blocking hydrogen diffusion paths along grain boundaries.
[0010] Step 3: Deposition of Si / B co-doped CrAlN / CrN superlattice support layer: By reactive magnetron sputtering of CrAl and Si targets, an interface is formed to block the crack propagation path, significantly improving the fracture toughness of the coating and avoiding brittle fracture under high pressure load. B2H6 is introduced to deposit a Si / B co-doped CrAlN / CrN superlattice with a superlattice period of 100nm. Si forms a dense amorphous Si3N4 network to fill the micropores and reduce porosity, while B improves high-temperature stability, delays thermal decomposition of the coating, and enhances corrosion resistance in acidic environments.
[0011] Step 4: Deposition of TiAlSiN-Y2O3 nanocomposite barrier layer: Y2O3 nanopowder is simultaneously injected into the TiAl target by cathodic arc to deposit the TiAlSiN-Y2O3 layer. The Y2O3 fills the microcracks in the coating and forms a passivation film, which double blocks the hydrogen permeation path and significantly improves the corrosion resistance in acidic environments.
[0012] Step 5: Gradient Ti-WC-DLC surface functional layer deposition: The bottom Ti / TiC layer is deposited by arc ion plating, the middle TiC-WC layer is deposited by magnetron sputtering, and the surface WC-DLC layer is deposited by PHC-PECVD. The acetylene flow rate is 20 sccm, the WC target current is 5A, and the pulsed microwave power is 2.5kW. Through the three-layer gradient, the bottom layer has a high modulus to match the support layer, the middle layer transitions the thermal expansion coefficient, and the surface WC-DLC layer provides ultimate hydrogen barrier and low friction characteristics.
[0013] Step 6, Fluorination and Hydrophobic Treatment: Fluorination is performed by introducing CF4 plasma at a flow rate of 5 sccm for 10 min to generate an F-DLC surface layer, which significantly improves hydrophobicity, reduces the adsorption of acidic condensate, lowers the coefficient of friction, and extends the life of the seal.
[0014] In the preferred step 1, the pulsed fiber laser has a wavelength of 1064 nm and a power of 200 W. The micro-pit array has a diameter of 20 ± 2 μm, a depth of 5 ± 0.5 μm, and a spacing of 50 μm. +The bias voltage for H2 mixed plasma etching was -500V, and the time was 30min.
[0015] In the preferred step 2, the target current is 120A, the bias voltage is -150V, the argon partial pressure is 0.5Pa, and the deposition rate is 15nm / s when multi-arc ion plating of the Cr layer; the target power is 5kW, the pulse bias voltage is -100V, and the frequency is 50kHz when magnetron sputtering of the WC-La2O3 layer; and the layer thickness ratio of the multi-arc ion plating of the Cr layer to the magnetron sputtering of the WC-La2O3 layer is 1:1.
[0016] In the preferred step 3, the bias voltage during reactive magnetron sputtering is -80V, the substrate temperature is maintained at 450±10℃, the B2H6 inlet flow rate is 2±0.1sccm, the B2H6 flow rate control adopts a closed-loop feedback system, the B content fluctuation is <0.3at.%, and the superlattice period error is <5nm.
[0017] In the preferred step 5, the middle TiC-WC layer is co-sputtered with a TiC target and a WC target, and PHC-PECVD is excited by a planar hollow cathode. The planar hollow cathode excitation achieves uniform coating of deep holes and ensures the consistency of coating on complex curved surfaces. The gas ratio C2H2 / Ar / H2 = 40 / 50 / 10 sccm, the CF4 addition amount is ≤5%, the vacuum degree is 0.3 Pa, the deposition rate is 300 nm / min, and the aspect ratio of deep hole coating is ≥20.
[0018] Preferred deposition followed by 200eV Ar + Beam bombardment of the plane for 2 minutes, and Ar + The beam current density is 2 mA / cm². 2 Ion bombardment eliminates interfacial micropores, promotes atomic diffusion and chemical bonding, significantly enhances interlayer bonding strength, and reduces internal stress in the coating while suppressing the risk of hydrogen-induced delamination.
[0019] The present invention also provides a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder, which is made using the above-mentioned preparation process for the PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder.
[0020] The technical effects and advantages of this invention are as follows:
[0021] This invention significantly enhances the adhesion between the film and the substrate through laser microtexturing and plasma activation, preventing coating peeling. Utilizing a multi-layer composite structure and rare-earth doping technology, it achieves an extremely dense coating structure, effectively blocking hydrogen permeation pathways and fundamentally suppressing hydrogen embrittlement. Gradient design and fluorination hydrophobic treatment impart a low coefficient of friction and superhydrophobicity to the surface, reducing wear and corrosion. Simultaneously, it balances high hardness, high toughness, and excellent corrosion resistance, comprehensively improving the reliability, durability, and safety of the cylinder block in high-pressure hydrogen environments. Furthermore, it offers advantages such as environmental friendliness and strong process controllability. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0023] This invention provides a process for preparing a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder, comprising the following steps:
[0024] Step 1, Substrate Laser Microtexturing and Plasma Activation: A pulsed fiber laser is used to fabricate a micro-dimple array on the cylinder liner and piston surface. The pulsed laser forms a regular microstructure on the cylinder surface, significantly increasing the coating contact area, providing mechanical interlocking anchor points, and enhancing the physical adhesion between the coating and the substrate; and then, through Ar… + / H2 hybrid plasma etching removes the oxide layer and generates a nanoscale activated surface; high-energy ion bombardment thoroughly removes the oxide layer and simultaneously generates a nanoscale activated surface, promoting atomic-level bonding of subsequent coatings and reducing the risk of interfacial hydrogen permeation; in step 1, the pulsed fiber laser has a wavelength of 1064 nm and a power of 200 W; the micro-pit array has a diameter of 20 ± 2 μm, a depth of 5 ± 0.5 μm, and a spacing of 50 μm; Ar + The bias voltage for H2 mixed plasma etching was -500V, and the time was 30min.
[0025] Step 2: Alternating Multi-Arc Sputtering Deposition of Transition Layer: A Cr layer is deposited alternately by multi-arc ion plating and magnetron sputtering of a WC-La2O3 layer for 3-5 cycles. The Cr layer provides high bonding strength, while the WC layer enhances hardness and thermal stability. This alternating deposition creates a gradient thermal expansion transition, alleviating interlayer stress. La2O3 is a rare-earth doped phase, and nanoscale dispersion is achieved through high-energy ball milling of the pre-composite target. The La2O3 / CeO2 nanoparticles are then combined with Cr / WC powder using high-energy ball milling. The target composition uniformity deviation is ≤1.5 at.%, and the ball-to-material ratio in the high-energy ball milling method is [not specified in the original text]. The ratio of rare earth nanoparticles to the target material was 10:1, the rotation speed was 300 rpm, and the time was 2 h. The uniform dispersion of rare earth nanoparticles in the target material was achieved through mechanochemical action, which refined the grain boundaries and formed hydrogen traps, blocking the hydrogen diffusion path along the grain boundaries. In step 2, the target current was 120 A, the bias voltage was -150 V, the argon partial pressure was 0.5 Pa, and the deposition rate was 15 nm / s when the Cr layer was deposited by multi-arc ion plating. The target power was 5 kW, the pulse bias voltage was -100 V, and the frequency was 50 kHz when the WC-La2O3 layer was sputtered by magnetron sputtering. The layer thickness ratio of the multi-arc ion plating Cr layer to the magnetron sputtered WC-La2O3 layer was 1:1.
[0026] Step 3: Deposition of Si / B co-doped CrAlN / CrN superlattice support layer: CrAl and Si targets are reactively sputtered to form an interface that inhibits crack propagation, significantly improving the coating's fracture toughness and preventing brittle fracture under high pressure. B₂H₆ is introduced to deposit a Si / B co-doped CrAlN / CrN superlattice with a superlattice period of 100 nm. Si forms a dense amorphous Si₃N₄ network to fill micropores, reducing porosity. B enhances high-temperature stability, delays thermal decomposition of the coating, and strengthens corrosion resistance in acidic environments. In Step 3, the bias voltage during reactive magnetron sputtering is -80V, the substrate temperature is maintained at 450±10℃, the B₂H₆ flow rate is 2±0.1 sccm, and the B₂H₆ flow rate control uses a closed-loop feedback system. The B content fluctuation is <0.3 at.%, and the superlattice period error is <5 nm.
[0027] Step 4: Deposition of TiAlSiN-Y2O3 nanocomposite barrier layer: Y2O3 nanopowder is simultaneously injected into the TiAl target by cathodic arc to deposit the TiAlSiN-Y2O3 layer. The Y2O3 fills the microcracks in the coating and forms a passivation film, which double blocks the hydrogen permeation path and significantly improves the corrosion resistance in acidic environments.
[0028] Step 5: Gradient Ti-WC-DLC surface functional layer deposition: The bottom Ti / TiC layer is deposited by arc ion plating, the middle TiC-WC layer is deposited by magnetron sputtering, and the surface WC-DLC layer is deposited by PHC-PECVD. The acetylene flow rate is 20 sccm, the WC target current is 5 A, and the pulsed microwave power is 2.5 kW. Through three gradient layers, the bottom layer has a high modulus to match the support layer, the middle layer transitions the thermal expansion coefficient, and the surface WC-DLC layer provides ultimate hydrogen barrier and low friction characteristics. In Step 5, the middle TiC-WC layer is co-sputtered by TiC target + WC target, and PHC-PECVD is excited by a planar hollow cathode. The planar hollow cathode excitation achieves uniform coating of deep holes and ensures the consistency of the coating on complex curved surfaces. The gas ratio C2H2 / Ar / H2 = 40 / 50 / 10 sccm, the CF4 addition is ≤5%, the vacuum degree is 0.3 Pa, the deposition rate is 300 nm / min, and the aspect ratio of deep hole coating is ≥20.
[0029] Step 6, Fluorination and Hydrophobic Treatment: Fluorination is performed by introducing CF4 plasma at a flow rate of 5 sccm for 10 min to generate an F-DLC surface layer, which significantly improves hydrophobicity, reduces the adsorption of acidic condensate, lowers the coefficient of friction, and extends the life of the seal.
[0030] This invention significantly enhances the adhesion between the film and the substrate through laser microtexturing and plasma activation, preventing coating peeling. Utilizing a multi-layer composite structure and rare-earth doping technology, it achieves an extremely dense coating structure, effectively blocking hydrogen permeation pathways and fundamentally suppressing hydrogen embrittlement. Gradient design and fluorination hydrophobic treatment impart a low coefficient of friction and superhydrophobicity to the surface, reducing wear and corrosion. Simultaneously, it balances high hardness, high toughness, and excellent corrosion resistance, comprehensively improving the reliability, durability, and safety of the cylinder block in high-pressure hydrogen environments. Furthermore, it offers advantages such as environmental friendliness and strong process controllability.
[0031] After deposition at 200 eVAr + Beam bombardment of the plane for 2 minutes, and Ar + The beam current density is 2 mA / cm². 2 Ion bombardment eliminates interfacial micropores, promotes atomic diffusion and chemical bonding, significantly enhances interlayer bonding strength, and reduces internal stress in the coating while suppressing the risk of hydrogen-induced delamination.
[0032] The cylinder block of the high-pressure reciprocating hydrogen compressor includes a crankshaft 1, a crankshaft connecting rod 2, a sealing ring 3, a drain port 4, an air inlet 5, a cylinder liner 6, a piston 7, and an air outlet 8. The PVD coating on the surface of the cylinder block of the high-pressure reciprocating hydrogen compressor is mainly applied to the surface of the cylinder liner 6 and the piston 7.
[0033] Core performance tests:
[0034] The core performance of the cylinder block piston and cylinder liner after the PVD coating on the surface of the high-pressure reciprocating hydrogen compressor of this application and the conventional coating were tested. The relevant data of the test methods and performance test results are shown in Table 1.
[0035] Table 1:
[0036]
[0037]
[0038] As shown in Table 1, the PVD coating on the cylinder surface of the high-pressure reciprocating hydrogen compressor of this application significantly outperforms traditional coatings in key performance indicators such as bonding strength, hydrogen permeability, coefficient of friction, acid corrosion resistance, surface roughness, and lifespan. Specifically, the bonding strength is increased by 125%, hydrogen permeability is reduced by 22 times, the coefficient of friction is reduced by 76%, the resistance to strong acid corrosion is increased by 400%, the surface roughness is reduced by 75%, and the lifespan is increased by 300%.
[0039] This demonstrates that the PVD coating of this application has achieved a comprehensive breakthrough in mechanical properties, hydrogen barrier properties, tribological properties, and corrosion resistance through its unique four-level gradient composite structure and material design, and can effectively solve the problems of hydrogen embrittlement, wear, and corrosion in high-pressure hydrogen environments.
[0040] Environmental adaptability test:
[0041] The performance of the cylinder block piston and cylinder liner under different operating conditions was tested after applying the PVD coating to the surface of the high-pressure reciprocating hydrogen compressor cylinder block of this application and the conventional coating. The relevant data on the test methods and performance test results are shown in Table 2.
[0042] Table 2:
[0043]
[0044]
[0045] As can be seen from the environmental adaptability test data in Table 2, the coating of this application exhibits excellent stability and durability under the harsh test conditions simulating actual working conditions.
[0046] In thermal shock cycling tests, no peeling or cracking occurred after 100 cycles, which is far superior to traditional CrN coatings; in high-pressure hydrogen aging tests, the mass loss was ≤0.03%, which is significantly lower than traditional coatings; in acidic abrasive environments, the annual wear rate is extremely low; its deep hole coating capability (film thickness uniformity deviation <5%) and energy efficiency improvement (friction power consumption reduced by 40%) are also unattainable by traditional processes.
[0047] This indicates that the coating of this application not only has excellent performance, but also has excellent engineering applicability, and can meet the long-term stable operation requirements of the compressor cylinder under complex and variable working conditions.
[0048] Routine performance testing:
[0049] The core performance of the cylinder block piston and cylinder liner after the PVD coating on the surface of the high-pressure reciprocating hydrogen compressor of this application and the conventional coating were tested. The relevant data on the testing methods and performance test results are shown in Table 3.
[0050] Table 3:
[0051]
[0052]
[0053] As can be seen from the routine performance test data in Table 3, the coating of this application surpasses traditional electroplating in all aspects of basic performance indicators such as adhesion, wear resistance, corrosion resistance, hardness, and thickness uniformity.
[0054] The adhesion reaches the 4B-5B level and the tensile strength is >15MPa; the wear resistance index is 1-2 orders of magnitude higher; the salt spray corrosion resistance time is more than 500 hours and can withstand 20 cycles of alternating test; the hardness can reach 2000-3000HV; the thickness uniformity control accuracy (±0.1μm) far exceeds that of electroplating process (±0.5μm).
[0055] This demonstrates the advanced nature of the PVD coating preparation process in this application, and its comprehensive performance indicators fully meet and exceed the stringent requirements of the high-pressure hydrogen compressor cylinder for surface coating.
[0056] This invention also provides a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder, which is prepared using the aforementioned process for preparing a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder, specifically:
[0057] A rare-earth modified Cr / WC nanolayer transition layer, a Si / B co-doped CrAlN / CrN superlattice support layer, a TiAlSiN-Y2O3 nanocomposite barrier layer, and a gradient Ti-WC-DLC surface functional layer are sequentially arranged from the base layer to the surface, forming a four-level gradient composite structure with a total thickness of 10-12.5 μm. The four-level structure forms a gradient thermal expansion coefficient (12 × 10⁻⁶). -6 / K to 5.5×10 -6 The structure ( / K) significantly reduces interlayer stress, avoiding the risk of exfoliation under alternating loads. Simultaneously, the quaternary structure forms a hydrogen diffusion barrier chain. The rare-earth-modified Cr / WC nanolayer transition layer enhances bonding strength and blocks hydrogen permeation from the matrix. The Si / B co-doped CrAlN / CrN superlattice support layer slows hydrogen permeation. The TiAlSiN-Y2O3 nanocomposite barrier layer fills microcracks and repairs defects. The gradient Ti-WC-DLC surface functional layer provides the ultimate hydrogen barrier, with a permeability ≤5×10⁻⁶. -11 m 2 / s, thereby reducing the risk of hydrogen embrittlement.
[0058] The rare-earth modified Cr / WC nanolayer transition layer has a thickness of 1-1.5 μm. Alternating Cr / WC deposition forms a nanolayer structure, enhancing the interfacial bonding strength between the coating and the substrate. La2O3 / CeO2 nanoparticles are incorporated, which refine grain boundaries and form hydrogen traps, blocking hydrogen diffusion pathways and increasing the hydrogen diffusion activation energy, significantly reducing the substrate's hydrogen embrittlement sensitivity. The WC content is gradually increased from 20 at.% to 50 at.%, achieving a gradual matching of the thermal expansion coefficient from the substrate steel to the coating by controlling the WC content. This significantly reduces thermal stress and avoids the risk of delamination under alternating loads. The thermal expansion coefficient of the rare-earth modified Cr / WC nanolayer transition layer is reduced from 12 × 10⁻⁶ for the substrate steel. -6 / K transition to 5.5×10 -6 / K, the weight percentage of La2O3 / CeO2 nanoparticles is 1-3 wt.%, and the particle size is ≤50 nm;
[0059] The Si / B co-doped CrAlN / CrN superlattice support layer has a thickness of 5.0-6.0 μm and is formed by the periodic alternating deposition of CrAlN and CrN. The periodic CrAlN / CrN interface inhibits crack propagation, significantly improving the fracture toughness of the coating and avoiding brittle fracture under high pressure. The thickness of CrAlN is 70 nm and the thickness of CrN is 30 nm. The Si content in the Si / B co-doped CrAlN / CrN superlattice support layer is 8 ± 0.5 at.% and the B content is 2 ± 0.3 at.%, with a fracture toughness KIC ≥ 3.5 MPa. 1 / 2 Si forms a dense amorphous network to fill micropores and reduce porosity; B improves high-temperature stability, which greatly extends the life of the coating in oxidizing and acidic environments.
[0060] The thickness of the TiAlSiN-Y2O3 nanocomposite barrier layer is 1.5-2.0 μm. It contains 5 vol.% Y2O3 nanoparticles, which block microcracks and form a passivation film, effectively blocking hydrogen permeation pathways and simultaneously improving corrosion resistance in acidic environments. The Si3N4 phase encapsulates the TiN and AlN grains. The Y2O3 nanoparticles have a particle size ≤20 nm, and the TiN and AlN grain sizes are ≤10 nm. The Si3N4 phase encapsulates the ultrafine grains, with the amorphous phase inhibiting grain boundary diffusion and the nanocrystals enhancing hardness, achieving a synergistic effect of hydrogen resistance and corrosion resistance. The TiAlSiN-Y2O3 nanocomposite barrier layer exhibits a mass loss of <0.02 mg / cm³ in an acidic environment with pH=2. 2 ;
[0061] The thickness of the gradient Ti-WC-DLC surface functional layer is 2.5-3.0 μm. The gradient Ti-WC-DLC surface functional layer consists of a bottom layer, a middle layer, and a top layer. The bottom layer is Ti / TiC, providing a high-modulus matching support layer and ensuring strong interfacial bonding. The middle layer is TiC-WC, and the top layer is WC-doped DLC. The hydrogen permeability of the gradient Ti-WC-DLC surface functional layer is ≤5×10⁻⁶. -11 m 2 / s, WC doping enhances hardness and hydrogen barrier properties, achieving ultra-low hydrogen permeability. The thickness ratio of Ti to TiC in the bottom layer is 1:1, the thickness ratio of TiC to WC in the middle layer is 1:1-1.2, and the WC content in the surface layer is 20±2 at.%.
[0062] The surface layer has a hydrogen content gradient distribution, consisting of sequentially arranged low-hydrogen tetrahedral amorphous carbon, medium-hydrogen aC:H, and high-hydrogen polymeric DLC. The low-hydrogen tetrahedral amorphous carbon has a sp... 3With a bond content greater than 70% and a hydrogen content of 18±2%, the hydrogen content of high-hydrogen polymer DLC is 30±3%, and the elastic modulus is ≤120GPa. Through gradient control of hydrogen content, the surface layer of low-hydrogen dense carbon blocks hydrogen gas, the bottom layer of high-hydrogen flexible carbon absorbs strain, and the internal stress gradient is optimized to suppress microcracks.
[0063] A TiC transition layer is generated between the TiAlSiN-Y2O3 nanocomposite barrier layer and the gradient Ti-WC-DLC surface functional layer through ion beam pretreatment. The thickness of the TiC transition layer is 50±5nm, the bonding strength is >65N, and the friction coefficient is ≤0.12. The generation of the TiC transition layer through ion beam pretreatment ensures strong interfacial bonding with the functional layer.
[0064] The functional layer on the gradient Ti-WC-DLC surface is fluorinated and hydrophobic. CF4 plasma is introduced and fluorinated for 10 min to generate a fluorinated DLC surface layer with a contact angle >110°. The fluorination treatment generates a hydrophobic surface layer, reducing the adsorption of acidic condensate, lowering the friction coefficient, and improving sealing reliability.
[0065] Finally, it should be noted that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A process for preparing a PVD coating on the surface of a high-pressure reciprocating hydrogen compressor cylinder, characterized in that: Includes the following steps, Step 1, Substrate Laser Microtexturing and Plasma Activation: A micro-dimple array is fabricated on the surface of the cylinder liner and piston using a pulsed fiber laser; and then activated by Ar... + / H2 hybrid plasma etching removes the oxide layer and generates a nanoscale activated surface; Step 2, Alternating deposition of transition layer by multi-arc-sputtering: The Cr layer is deposited alternately by multi-arc ion plating and magnetron sputtering WC-La2O3 layer for 3-5 cycles, where La2O3 is a rare earth doped phase, and nanoscale dispersion is achieved by high-energy ball milling of pre-composite target material; Step 3, Si / B co-doped CrAlN / CrN superlattice support layer deposition: Si / B co-doped CrAlN / CrN superlattice is deposited by reactive magnetron sputtering of CrAl and Si targets and introducing B2H6. The superlattice period is 100nm. Step 4: Deposition of TiAlSiN-Y2O3 nanocomposite barrier layer: Y2O3 nanopowder is simultaneously injected into the TiAl target by cathode arc to deposit the TiAlSiN-Y2O3 layer; Step 5: Gradient Ti-WC-DLC surface functional layer deposition: The bottom Ti / TiC layer is deposited by arc ion plating, the middle TiC-WC layer is deposited by magnetron sputtering, and the surface WC-DLC layer is deposited by PHC-PECVD. The acetylene flow rate is 20 sccm, the WC target current is 5A, and the pulsed microwave power is 2.5kW. Step 6, Fluorination and Hydrophobic Treatment: Fluoride with CF4 plasma at a flow rate of 5 sccm for 10 min to generate F-DLC surface layer.
2. The preparation process of the PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor according to claim 1, characterized in that: In step 1, the pulsed fiber laser has a wavelength of 1064 nm and a power of 200 W. The micro-pit array has a diameter of 20 ± 2 μm, a depth of 5 ± 0.5 μm, and a spacing of 50 μm. + The bias voltage for H2 mixed plasma etching was -500V, and the time was 30min.
3. The preparation process of the PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor according to claim 1, characterized in that: In step 2, the target current for multi-arc ion plating of the Cr layer is 120A, the bias voltage is -150V, the argon partial pressure is 0.5Pa, and the deposition rate is 15nm / s. When magnetron sputtering the WC-La2O3 layer, the target power is 5kW, the pulse bias voltage is -100V, and the frequency is 50kHz. The layer thickness ratio of the multi-arc ion plating of the Cr layer to the magnetron sputtering of the WC-La2O3 layer is 1:
1.
4. The preparation process of the PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor according to claim 1, characterized in that: In step 3, the bias voltage during reactive magnetron sputtering is -80V, the substrate temperature is maintained at 450±10℃, and the B2H6 inlet flow rate is 2±0.1sccm.
5. The preparation process of the PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor according to claim 1, characterized in that: In step 5, the middle TiC-WC layer is co-sputtered with a TiC target and a WC target, and the PHC-PECVD is excited by a planar hollow cathode. The gas ratio C2H2 / Ar / H2 = 40 / 50 / 10 sccm, the CF4 addition amount is ≤5%, the vacuum degree is 0.3 Pa, the deposition rate is 300 nm / min, and the aspect ratio of the deep hole coating is ≥20.
6. The preparation process of the PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor according to claim 1, characterized in that: After deposition, Ar200eV + Beam bombardment of the plane for 2 minutes, and Ar + The beam current density is 2 mA / cm². 2 .
7. A PVD coating on the surface of the cylinder block of a high-pressure reciprocating hydrogen compressor, characterized in that: It is made using the PVD coating process described in any one of claims 1-6 for the cylinder surface of a high-pressure reciprocating hydrogen compressor.